UPAYA MENINGKATKAN KETERAMPILAN BERTANYA MELALUI PENERAPAN PEMBELAJARAN BERBASIS SNOWBALL THROWING - sukerni, putu (Journal of Education Action Research, 2018)
This research is based on the low skill of asking students in grade I SD Negeri 4 Kaliuntu. This study aims to increase the ability to ask questions of students with the implementation of learning model of snowball throwing of first grade students in SD Negeri 4 Kaliuntu, Buleleng sub-district, Buleleng regency year 2015/2016. This research was a classroom action research conducted in two cycles. Each cycle consists of planning, action, observation / evaluation, and reflection. The subjects of this study were the first grade students in SD Negeri 4 Kaliuntu, Buleleng District, Buleleng Regency in 2015/2016 school year as many as 41 students. Data collection in this research is done by using observation sheet. The data collected were analyzed using descriptive statistical analysis method and quantitative descriptive analysis. The result of the research shows that thematic learning using snowball throwing model can improve the ability to ask questions of first grade students in SD Negeri 4 Kaliuntu, Buleleng District, Buleleng Regency in the 2015/2016 . In the first cycle, the students skill question ws 58.2% in the less category and increased to 81.4% in cycle II which is in the good category.